Sikap Dan Pengetahuan Terhadap Jamu Di Komunitas Yoga First Klaten - Ahda Maulida; Indri Kusuma Dewi; Susilo Yulianto (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
Jamu can improve health for the body empirically. The use of jamu has a tendency to back to nature. Jamu is a traditional medicine of Indonesia. Based on preliminary study about attitude and knowledge towards jamu in Yoga First Klaten by interviewing members, there were 5 of 7 members showed positive attitude towards jamu and 3 of 7 members knew about boiled traditional jamu. The goal of this research is to know attitude and knowledge towards jamu in Yoga First Klaten Community. The kind of the research is quantitative descriptive. Samples were taken by using purposive sampling, there were 50 samples and data was gotten from respondens that fill in the attitude and knowledge towards jamu statement form. The result of attitude has shown that 100% repondens were kind towards jamu. The result of knowledge has shown that 90% respondens in a good category and 10% in a enough category towards jamu. The conclusion is 100% respondens were kind and 90% respondens in a good category towards jamu.